Analysis Of The Role Of The Office Of Religious Affairs In Managing The Case Of Siri Marriage Couples - Debi Sintia Dali; Sri Nanang Meiske Kamba; Nurul Fazri Elfikri (Universitas Negeri Gorontalo, 2022)
The purpose of this study is to find out and analyze how the role of the religious affairs office in dealing with Siri marriages in the North City District. The method used in this research is an interviews, observation, and documentation. This type of research is descriptive and qualitative. The qualitative descriptive analysis approach emphasizes research that aims to obtain legal knowledge empirically by going directly to the object or field. The types of data used in this study are primary and secondary data. The results of the study indicate that the role of the religious affairs office in tackling Siri marriages in the District of North City includes providing counseling on marriage registration and happy families to prospective brides and guardians, conducting socialization about the impact of unregistered marriages, and also the importance of registering marriages carried out in every time he fills an event, either a recitation or an event that involves the head of the religious affairs office. Factors that hinder the religious affairs office in dealing with unregistered marriages in the North City sub-district include Lack of competent human resources, low awareness of the law in society, and inadequate facilities and infrastructure.